2015
DOI: 10.1016/j.ijsu.2015.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Update on the efficacy of extracorporeal shockwave treatment for myofascial pain syndrome and fibromyalgia

Abstract: Chronic muscle pain syndrome is one of the main causes of musculoskeletal pathologies requiring treatment. Many terms have been used in the past to describe painful muscular syndromes in the absence of evident local nociception such as myogelosis, muscle hardening, myalgia, muscular rheumatism, fibrositis or myofascial trigger point with or without referred pain. If it persists over six months or more, it often becomes therapy resistant and frequently results in chronic generalized pain, characterized by a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 31 publications
0
48
0
2
Order By: Relevance
“…[9][10][11][12][13][14] Extracorporeal Shock Wave Therapy (ESWT) can be nowadays approved as an effective, safe, noninvasive therapy for many musculoskeletal diseases and many conditions where regenerative effects are desirable. It is the novel therapy for applications in the fields of regenerative medicine, tissue engineering and cell therapies.…”
Section: -14mentioning
confidence: 99%
See 3 more Smart Citations
“…[9][10][11][12][13][14] Extracorporeal Shock Wave Therapy (ESWT) can be nowadays approved as an effective, safe, noninvasive therapy for many musculoskeletal diseases and many conditions where regenerative effects are desirable. It is the novel therapy for applications in the fields of regenerative medicine, tissue engineering and cell therapies.…”
Section: -14mentioning
confidence: 99%
“…[9][10][11][12][13][14] b. Shock waves effect on soft tissue and musculoskeletal tissue are as the follows i.…”
Section: -14mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there are evidences of free nerve endings degeneration and transient dysfunction of nerve excitability at the neuromuscular junction, a pure mechanism of breaking-up the actin myosin links with the overstimulation lead to a diminished transmission of pain signals to the brainstem. For pain transmission, in animal studies revealed substance P, calcitonin gene-related peptide (CGRP) expression in the dorsal root ganglion and on neurovascular sprouting [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%